Attention biases and social-emotional development in preschool-aged children who have been exposed to domestic violence. (March 2019) - Mastorakos, Tessie; Scott, Katreena L.
Abstract: Background: School-aged children and adolescents exposed to domestic violence (DV) disproportionality attend to threatening and sad cues in their environment. This bias in attention has been found to predict elevations in symptoms of psychopathology. Studies have yet to explore attention biases using eyetracking technology in preschool-aged children with DV exposure. Objective: This study investigated whether preschool-aged children exposed to DV show vigilance to angry and sad faces versus happy faces and a target non-face stimulus relative to non-exposed children, and whether such vigilance relates to child social-emotional development. Participants and setting: Preschool-aged children were recruited from a large, diverse, urban community. DV-exposed children were recruited from a dyadic, mother-child treatment group specifically designed for, and restricted to, mothers who have experienced domestic violence (DV-exposed group, n = 23). Children with no prior exposure to DV and their mothers were recruited within the same community (non-exposed group, n = 32). Methods: Children completed an eye-tracking task to assess their attention to face stimuli and mothers rated their children's social-emotional development. Total duration of fixations were analyzed. Results: Results showed that DV-exposed children have a significantly stronger attention bias away from sad faces ( p = 0.03; d = 0.62) and neutral faces ( p = 0.02; d = 0.70) relative to non-exposed children, and this attention bias away from sad and neutral faces is associated with child social-emotional problems. Contrary to our hypothesis, no bias towards anger was found for DV-exposed versus non-exposed children. Conclusions: This study contributes to growing evidence that young children's negative attention biases influence functioning and have important implications for children's well-being and development.